Application of modified atmosphere for packaging of ripened sausages: influence on volatile compounds evolution - Summo, Carmine; Caponio, Francesco; Paradiso, Vito Michele; Tricarico, Francesco; Cosmai, Lucrezia; Gomes, Tommaso (Progress in Nutrition, 2014)
An experimental investigation was carried out to assess the effect of the packaging atmosphere composition on the evolution of volatile compounds in ripened sausages during storage. To the aim, three atmosphere compositions, characterized by different N2:CO2 ratio (ATM1, 70:30; ATM2, 80:20; ATM3 95:5) were applied for the packaging of ripened sausages. All the packed, not-sliced, sausages were stored in the dark at 4°C for 5 months. The determination of volatile compounds by SPME/GC/MS was carried out on the samples after each month of storage. The obtained results pointed out that the majority of volatile compounds resulted significantly related to the storage time variable more than to the atmosphere variable. However, some volatile compounds, derived from the lipid auto-oxidation such as nonanoic acid and octanoic acid, were significantly influenced by the atmospheres composition, with values that were lower in ATM1.